Effects of electrodes length and insulation for transcranial electric stimulation - Tomio, Ryosuke (Surg Neurol Int, 2019)
BACKGROUND: The aim of this study is to investigate the effects of length and insulation of the corkscrew electrodes for transcranial motor evoked potential (tMEP) monitoring. METHODS: We used the finite element method to visualize the electric field in the brain, which was generated by electrodes of different lengths (4, 7, and 12 mm). Two types of head models were generated: A model that included a subcutaneous fat layer and another without a fat layer. Two insulated needle types of conductive tip (5 and 2 mm) were studied. The stimulation threshold levels of hand tMEP were measured in a clinical setting to compare normal corkscrew and insulated 7-mm depth corkscrew. RESULTS: The electric field in the brain depended on the electrode depths in the no fat layer model. The deeper the electrodes reached, the stronger the electric fields generated. Electrode insulation made a difference in the fat layer models. The threshold level recordings of tMEP revealed that the 7-mm insulated electrodes showed a lower threshold than the normal electrodes by one-side replacement in each patient: 33.6 ± 9.6 mA and 36.3 ± 11.0 mA (n =16, P < 0.001), respectively. The 7-mm insulated electrodes also showed a lower threshold than the normal electrodes when both sides, electrodes were replaced: 34.4 ± 8.6 mA and 37.5 ± 9.2 mA (n =10, P = 0.003), respectively. CONCLUSIONS: The electrodes depth reached enough to skull is considered to be efficient. Insulation of the electrodes with a conductive tip is efficient when there is subcutaneous fat layer.